The perception of Naturology students from inhaling the pink pepper essential oil (Schinus terebinthifolius Raddi). (14th July 2021) - Huei Zago Wang, Juliana; Kozuchovski Daré, Patricia; Armiliato Emer, Aline
Abstract: Schinus terebinthifolius Raddi (Brazilian pepper tree or 'aroeira') is a native Brazilian tree, which its different parts are used medicinally for several applications, and its fruits are known as pink pepper. Composed mainly by monoterpenes, pink pepper's essential oil (EOpp) presents cytotoxic, antioxidant, insecticidal, cicatrizant, fungicidal, bactericidal and antimicrobial activity. It is known that there exists some literature, which describes psycho‐emotional effects, as well as symbolic aspects related to the use of essential oils (EOs) in clinical practice. However, there is a lack of current scientific studies that address these effects described in the literature, resulting from the stimulus via inhalation, as well as if it can interfere in the effectiveness of treatments with EOs. This research aimed to describe the perceptions and psychological associations of UNISUL's students of Naturology, when inhaling EOpp. This is a qualitative, descriptive, exploratory and field research. This research was conducted with 30 participants in individual in‐depth interviews. The inhalation of EOpp was related to the perception of physical sensations such as relaxation, sedation and improvement of breathing, as well as discomfort in the respiratory system, such as nose stinging; childhood memories and other past recollections, feelings of comfort, welcome, warmth, tranquility, calm, well‐being and peace; and improvement of self‐perception, sense of presence and decreased thoughts. It was possible to conclude that most of the feelings and emotions expressed by the interviewed participants were more directly related to the physical sensations and memories that emerged with the inhalation of EOpp, than with EOpp itself. Abstract : In this study 30 naturology students received an olfactory tape with a drop of Schinus terebinthifolius Raddi essential oil, they inhaled it and then reported their perceptions. As a result, they related relaxation, sedation, breathing improvement, nausea, loss of appetite, childhood memories, improvement of feeling of presence and decrease of thoughts, and others.